2014
DOI: 10.1519/jsc.0000000000000428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Group-Based Step Aerobics Training on Sleep Quality and Melatonin Levels in Sleep-Impaired Postmenopausal Women

Abstract: The purpose of this study was to investigate the effect of regular moderate- to high-intensity step aerobics training on the melatonin levels and sleep quality of sleep-impaired postmenopausal women (PMW). PMW with poor sleep (having a score over 5 in the Chinese version of the Pittsburgh sleep quality index [PSQI]) were divided into a training group (TG, n = 10) and an age-, height-, weight-, and PSQI score-matched control group (CG, n = 9). The participants in the TG performed 40-45 minutes of step aerobics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 34 publications
0
20
0
4
Order By: Relevance
“…Both melatonin [37] and cortisol [39] are related to sleep and activity cycles and the disruption of their daily cycle could have a direct effect on diurnal activity patterns. Furthermore, aerobic fitness has been shown to reduce levels of cortisol [40] and increase melatonin in the blood [41]. The study of diurnal activity patterns in subjects with different hormonal profiles could provide further insight into the age-related decline in physical activity and help the development of more effective intervention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Both melatonin [37] and cortisol [39] are related to sleep and activity cycles and the disruption of their daily cycle could have a direct effect on diurnal activity patterns. Furthermore, aerobic fitness has been shown to reduce levels of cortisol [40] and increase melatonin in the blood [41]. The study of diurnal activity patterns in subjects with different hormonal profiles could provide further insight into the age-related decline in physical activity and help the development of more effective intervention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that chronic moderate to high-intensity physical exercise interventions (step aerobics exercise 3 times/week/10 weeks at an intensity of 75-85% of the heart rate reserve during 45 min) modified the circadian rhythm, which is related with melatonin levels of individuals [31]. Opposite findings have been described by showing that low-intensity/chronic physical exercise exerts negative effects on the secretion of melatonin [32].…”
Section: Physical Exercisementioning
confidence: 99%
“…Cai et al [4] confirmed that a 10-week, moderate-to-high intensity training program can improve sleep quality and increase melatonin level in sleep-impaired, postmenstrual women. Another significant benefit of step exercise is improvement in bone density, which decreases the risk of osteoporosis [46,39,22].…”
Section: Introductionmentioning
confidence: 96%